Behavior of Photo Induced Minority Carrier Lifetime in PN Junction with Different Bias Voltages. (December 2015) - Sameshima, T.; Hasumi, M.
Abstract: We report analysis of the photo-induced minority carrier effective lifetime (τeff ) in a p + n junction formed on the top surfaces of a n -type silicon substrate by ion implantation of boron and phosphorus atoms at the top and bottom surfaces followed by activation by microwave heating. Bias voltages were applied to the p + boron-doped surface with n + phosphorus-doped surface kept at 0 V. The values of τeff were lower than 1×10 -5 s under the reverse-bias condition. On the other hand, τeff markedly increased to 1.4×10 -4 s as the forward bias voltage increased to 0.7 V and then it levelled off when continuous-wave 635 nm light was illuminated at 0.74 mW/cm 2 on the p + surface. The carrier annihilation velocity S p+ at the p + surface region decreased from 4000 to 265 cm/s as the forward bias voltage increased from 0 to 0.7 V. τeff also increased from 1.4×10 -5 to 1.0×10 -4 s as the intensity of 635 nm light increased from 0.04 to 0.74 mW/cm 2 under the open-circuit condition.